Home Ventilation in Children - Gupta, D; Sachdev, A; Gupta, N; Simalti, AK (Journal of Nepal Paediatric Society, 2015)
Introduction: Home mechanical ventilation (HMV) can prolong survival and improve quality of life. The objectives were to review the challenges, clinical conditions and outcome of children who were discharged from the hospital on respiratory support. Material and Methods: Twenty four patients, who were electively discharged from PICU and had received home ventilatory support for more than 15 days, were enrolled over 11 year study period. Patients were followed up monthly, for two years, for ventilatory requirements, any problems encountered during previous month and for any complication. Results: Twenty four patients with a median age of 3.5 years were discharged home with ventilatory support. HMV was started in 2001 at our hospital. Patents received home ventilation for a median period 5.4 months. Twenty (83.3%) patients received invasive mechanical ventilation via tracheostomy and four (16.7%) patients received non-invasive mechanical ventilation. Twelve (50%) patients received ventilatory support for more than 20 hrs a day and twelve (50%) patients received only during sleep. On follow up for two years for each patient, twenty (83.3%) patients successfully came off from ventilatory support while, two (8.3%) patients died and two (8.3%) lost to follow-up. Conclusion: HMV can be safely applied in selected children with CRF after providing adequate training to the care givers. For its more efficient use, we need to have good social support and medical assistance which can be extended to their homes to meet their complete health care needs. J Nepal Paediatr Soc 2015;35(1):85-88